Examining behavioural intentions on online hotel booking among Malaysian guests - Amin, Dawood Ismail (2021)
The development in Information and Communication Technology (ICT) has changed the distribution channels in the hotel industry. Virtual platforms, such as hotel websites, have become a major channel for customers’ communication, marketing and selling points. Previous studies discuss the benefits of ICT to hoteliers and their customers. The hotel websites provide customers with a tremendous volume of information such as room rates, hotel features, visualized presentations and customers’ reviews. On the other hand, hotel operators can reduce the distribution costs by reaching their customers directly and targeting a bigger market share. Nevertheless, online hotel booking is different from purchasing a product from the Internet because the hotel industry has to deal with a complex issue, which is intangibility. The consumers might not be sure whether the hotel rooms will match their expectations or not. Therefore, researchers have argued that hoteliers need to develop their websites to attract customers through visual presentations and online reviews. However, it is not clear how visual presentations and online reviews jointly influence online consumers’ behaviour toward hotel booking. Moreover, understanding how hotel customers behave toward online hotel booking is indispensable as the behaviours of hotel consumers change along with the changes in the ICT world. Although most of the previous studies investigating the relationships between various factors and consumers behaviour for online hotel booking were published in leading publications, very little research has ii explored the impact of visual presentation and online reviews within the context of Malaysian hotel customers. Therefore, this research tends to fill the gaps in the literature by exploring the influence of visual presentations and online reviews on consumers’ behaviour toward online hotel booking from the point of Malaysian customers. The study integrates visual presentations and online reviews with the technology acceptance model (TAM). A quantitative approach is applied in the current research, and partial least squares structural equation modelling is used to test the proposed hypotheses. The research model is examined based on a sample of 374 respondents from Malaysia, which is collected from an online survey. The results show that booking intention is mainly determined by perceived usefulness and perceived enjoyment. Besides, the statistical analysis supports the notion that visual presentations and online reviews have a positive impact on perceived usefulness, perceived ease of use, and perceived enjoyment. However, neither of them has any significant influence on booking intention directly. Finally, the study concludes that online consumers are more likely to book a hotel online if visual presentations and online reviews appear to be useful and enjoyable.